Analisis Butir Soal Uraian Bernuansa Etnososial pada Materi IPS Kelas V Sekolah Dasar - Setiyadi, Desi; Suharini, Erni; Widiyatmoko, Arif (FONDATIA, 2025)
The main problem in this study is the lack of optimal integration of socio-ethnic values in the test items, which potentially hinders students' understanding of the local socio-cultural context. This study aims to analyze the essay test items with a socio-ethnic nuance in the Social Studies material for fifth-grade elementary school students, focusing on validity, reliability, discrimination power, difficulty level, and representation of socio-ethnic values. The method used is quantitative with a descriptive-analytical approach. The instruments used are essay test items that have been developed and validated by experts. Data analysis was conducted using statistical analysis techniques to measure validity, reliability, discrimination power, and difficulty level of the items, as well as a qualitative approach to assess the representation of socio-ethnic values. The results indicate that most items have met the criteria for high validity and reliability; however, there are several items with a relatively high difficulty level and low discrimination power. The representation of socio-ethnic values in the items was also well identified, although there is still room to strengthen the integration of local culture in the test items. The impact of this research is an increased awareness of the importance of socio-ethnic values in elementary education, which can help students understand and appreciate Indonesia's cultural diversity in a more inclusive and contextual educational setting.